A Study on the Artistic Expression of Cross-Border Ethnic Music Culture: A Case Study of the Chinese Russian Musical Ergun Love - Song, Nianze (International Journal of Literature and Arts Studies, 2026)
This article takes the Chinese Russian ethnic musical Ergun Love as its primary research object. Drawing on Stuart Hall’s theory of representation and engaging with scholarship on memory and ritual music, it examines how cross-border ethnic music culture is artistically expressed in contemporary stage works. The analysis focuses on four interrelated dimensions: the representation of love as a core narrative theme, the construction of collective memory through traditional folk songs, the staged presentation of ritual culture, and the integration of multi-ethnic musical elements. The study demonstrates that Ergun Love enters the emotional world of the Chinese Russian ethnic group through a love-centered narrative that mediates individual affection and collective identity. It constructs sonic memory via the thematic deployment and recurrent appearance of traditional folk songs, which function as carriers of history and cultural continuity. Ritual culture is presented through dramatized scenes such as weddings and birthdays, where music, gesture, and staging jointly encode social norms and symbolic meanings. Furthermore, the incorporation of traditional Chinese modes and Mongolian musical elements reveals the composite and frontier character of the Ergun cultural space. By transforming emotional experience, folk traditions, musical memory, and frontier life scenes rooted in local social practice into a visible and communicable stage text, the work accomplishes the artistic construction of the cultural image of the Chinese Russian ethnic group. The article argues that Ergun Love not only enriches musical theatre on Chinese Russian themes, but also exemplifies a broader pathway for transforming and expressing cross-border ethnic music culture in contemporary artistic contexts, offering a valuable case for the stage-based study of small-population and cross-border ethnic groups.